Effect of a supervised exercise program on overweight and obese adolescents: a quasi-experimental study. (14th October 2021) - Lopes, J; Jove Cesar, D; Oliveira, A L P; Silva, A F P V; Biasi, B L; Santos, V B; Silva, R P M
Abstract: Background: Obesity and overweight are a worldwide public health problem, and physical exercise is an important intervention to reduce these high rates. Supervised exercise programs have significant impacts on the prevalence of obesity in adolescentes and the nurses should guide on the importance of physical activity. Purpose: To evaluate the effect of an exercise program on the profile of obesity and overweight in adolescents. Methods: Quasi-experimental study based on TREND guidelines. Performed with 72 adolescents, who underwent a physical activity program supervised (aerobic and resistance physical exercises) by a health professional 5 times a week, each session lasting from 50 to 60 minutes. The population consisted of all obese and overweight adolescents, aged between 14 and 18 years, who were authorized by the doctor to perform physical activity, and who did not have physical mobility problems and/or cognitive alterations. Adolescents with an anthropometric index greater than or equal to the z +1 score, and waist circumference greater than the 90th percentile, and/or skinfolds greater than the 90th percentile were considered obese or overweight. Adolescents who did not perform outcome assessments before and after the intervention, or those who did not attend physical exercise sessions for a week were excluded. The primary outcomes were anthropometric measurements (body mass index, tricipital and subscapular skinfolds, estimated body fat percentage, brachial perimeter, arm fat area, waist and neck circumference measurement), while secondary outcomes were lipid profile, capillary glycemia and blood pressure. Outcomes were assessed before and the day after the program ended. The effect of the program in relation to the outcomes was analyzed using appropriate statistical tests, with p<0.05 being considered significant. Results: A total 520 adolescents were assessed for eligibility; of these, 129 were considered eligible and 124 agreed to participate in the study, but 20 gave up participating. Therefore, 104 started the intervention and 32 adolescents were excluded over time, as they did not show up for a week in the exercise program, which totaled 72 adolescents for analysis. A significant improvement was observed in all primary outcomes analyzed (p<0.001) and in most secondary outcomes (capillary blood glucose, p=0.0001; triglycerides, p=0.0001; systolic blood pressure, p=0.005) after 12 weeks of the supervised physical exercise program. Conclusion: The supervised physical exercise program showed a significant reduction in anthropometric measurements, as well as in glycemic, triglyceride and blood pressure levels. To prove the effect of physical exercise on adolescents may impact public and educational policy measures and the incorporation of this practice in adolescents' school life. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Conselho Nacional de Desenvolvimento Científico e Tecnolόgico (CNPq)